Entry-rates, the share of surviving businesses and employment growth: differences between West and East Germany since unification - Reinhold Grotz; Udo Brixy (European Regional Science Association (ERSA), 2002)
Entry-Rates, survival-rates and growth-rates vary considerably between regions. The aim of our paper is firstly to point out these differences in Germany as a whole. It will be shown how these three parameters work together. Are there regions in which all three are favourable for newly founded firms? Sternberg (2000) states that it is to be expected that in regions with high rates of entry the survival-rates should be high, too. This is because a convenient environment for the founding of new firms should be equally favourable for the further development of these firms. With a database that covers all newly founded establishments since 1983 (West-Germany) resp. 1992 (East-Germany), cohorts of each year can be analysed until the year 2000. In a second step we will analyse east - west differences since the unification. Newly founded firms are of outstanding importance for the development of the market economy in eastern Germany. The transition of the economic system came as a shock to existing firms and led to an enormous boom in the establishment of new firms. Brixy & Kohaut (1999) showed that shortly after unification a kind of 'start-window' existed during which the conditions for establishment, growth and survival of new firms were extraordinarily good. Now 12 years after the unification it can be shown, that founding-rates, growth-rates and survival-rates in both parts of Germany came into line. But there are sizeable regional differences in both parts. A in-depths comparison gives the possibility to compare the performance of special types of business over time and space in different cohorts. This should lead to a better understanding of the regional problems faced by regional economies.
Keywords: 330